Inferências sobre a inserção incremental de modelagem paramétrica no processo de projeto em arquitetura com abordagem biomimética: cognição e forma - Silva, Ágabo Carvalho (2020)
The design process in architecture is considered by many authors (FABRICIO and MOREIRA, 2011; KOWALTOWSKI et al. 2011) as something complex to be understood and with variables that are difficult to measure from the point of view of decisions, in view of subjective relations against standards and norms instituted by procedures adopted over time. With the development of digital technologies and the possibilities of design exploration with more integrated approaches to the natural environment, especially in the field of architecture, new ways of designing and conceiving objects were developed, which until then, due to the lack of adequate tools, were limited or unthinkable. In this context, we highlight the use of parametric modeling and biomimetics, as instruments capable of driving an innovation, whether in proposing new creative processes, or in the control of structures and documentary design information. However, its wider dissemination with the incorporation of hybrid processes, has encountered some difficulties, given the lack of computational instruction among professionals, in addition to an absence of epistemology about the real potential of computers as a creative tool (TERZIDIS, 2006) . This absence of a treaty on the capacities and biases produced by the use of computing can be understood as a gap not yet completely filled in Computational Design, since there is no clarity about the real impacts for the design practice. This research proposes a qualitative and experimental approach, in order to elucidate specific questions of the project learning process with an experience developed in two stages and with two different groups. A directed literature review and a didactic experiment were combined, which discusses and compares correlated aspects about the use of traditional and digital design strategies, the latter with an emphasis on methods that integrate parametric and biomimetic architecture. It was found that there is a propensity for the hybrid use (manual and digital tools) of the tools to support the project, and that parametric modeling proved to be an important support resource in proposing different alternatives or solutions if considering the formal aspect. The cognitive barriers in relation to the limitation of expression and representation for the design process, was a variant that proved challenging from the point of view of implementation, either by the context of training, or by the context of professional practice. However, with promising prospects for improvement and innovation in creative processes, showing itself as an area in need of further investigation.